Effect of adhesive systems, direct resin composites and artificial aging on tensile bond strength between different resin composites and human dentin. (July 2021) - Steiner, René; Schwarz, Vincent; Schnabl, Dagmar; Edelhoff, Daniel; Stawarczyk, Bogna
Abstract: Purpose: The purpose of this study was to evaluate the tensile bond strength of universal, flowable and bulk-fill resin composites on dentin using different adhesive systems and after artificial aging. Materials and methods: 360 extracted human wisdom teeth were prepared to specimens and divided into 36 groups (n=10). One half of the specimens (180) were treated by using one-step adhesive systems and the other half (180) with multi-step adhesive systems. Sleeves where placed on the dentin and filled with either universal, flowable or bulk-fill resin composite. Tensile bond strengths were measured after 24 h water storage and after thermal cycling (10, 000x, 5°C–55 °C). Fracture types were analyzed by stereomicroscope. The data were analyzed using Kolmogorov-Smirnov, three- and one-way ANOVA followed by the Scheffé post-hoc test, unpaired two-sample t -test and Chi 2 test (p < 0.05). Results: The type of the resin composite had the strongest influence on tensile bond strength (partial eta squared ηP 2 =0.648, p < 0.001) followed by the adhesive system (ηP 2 =0.372, p < 0.001) and the artificial aging (ηP 2 =0.259, p < 0.001). Flowable composite resins showed higher tensile bond strengths than universal and bulk-fill composite resins. Multi-step adhesives obtained higher bond strength values than the one-step ones. Tensile bond strength decreased after artificial aging. Flowable resin composites showed mostly cohesive fractures, whereas the adhesive fracture type predominated in the universal and bulk-fill composite groups. Conclusion: The combination of flowable resin composites and multi-step adhesives is recommended. The high number of cohesive fractures in the flowable groups underlines the strong adhesion of flowable resin composites to dentin.